Features of Teaching Medical Chemistry to Foreign Students (Eurasian Medical Research Periodical, 2022)
The issues of teaching medical chemistry in English to foreign students studying at the Bukhara State Medical Institute have been examined in the article. The specificity of teaching medical chemistry is analysed and the department’s experience in preventing emerging problems for the successful implementation of training is presented